ROLE OF COLLABORATORS AND MERCENARIES IN THE BIDA LED WARS IN AFEMAI LAND 1860-1897 - Jimoh, Sedenu A. (IJRDO - Journal of Social Science and Humanities Research, 2022)
In the second half of the 19th Century, the inhabitants of the three geographical regions of Afemai land experienced sporadic but coordinated military attacks organized by the Bida Jihadists whose primary objective was to take advantage of the human and economic potentials of the Afemai. In spite of their resoluteness and gallantry in defending their sovereignty, the indigenes like most other communities in the Niger-Benue confluence area were forced to surrender to the highly mobile and tactical military of Bida. Factors responsible for the defeat suffered by the Afemai have become an issue of controversy within academic circles and among traditions who blame the intimidating military and superior weapons deployed by the invaders against the indigenous warriors as reason for the defeat. This paper aver that the successful invasion and subsequent conquest of Afemai by the enemy has more to do with the assistance received from indigenous and external collaborators who provided the Bida with all the information, logistics and other military supports required to achieve their annexation plot. In analyzing this aspect of the Jihad in Afemai which has been relatively neglected, certain perceptible issues that enriched our knowledge on the general trend of events and missing in previous studies are brought to the fore.